The Kinetics of White Blood Cells in Acute Dengue Infection - Mohd Nasrul Bin Mohd Ghazali; Umi Solekhah Intansari; Ida Safitri Laksanawati (Pusat Kedokteran Tropis, 2013)
ABSTRACTIntroduction: Dengue is a mosquito borne viral febrile illness with a high incidence rate of approximately 50 million cases of infection world wide every year. Dengue virus can infect many cells, e.g. monocytes, dendritic cells, Kuppfer cells, B cells including bone marrow and lung. Leukocytes plays an important roles in eliminating dengue virus especially monocytes. However, dengue virus sometimes attack the monocytes and uses them for replication causing monocyte to unde go apoptosis in order to prevent spreading by certain mechanisms.Objectives: To explore the difference in white blood cells count in acute dengue patients from day 2 to day 6.Methods: This research is conducted in a cross sectional observational study method by recording the WBC count, Lymphocytes count, Neutrophils Count, Relative Monocytes Count, and Absolute Monocytes Count from NS-1 positive dengue infection patient using the hematology analyzer. The data was taken from day 2 to day 6 of the fever. One-way ANOVA test was used and a p value <0.05 was considered as significant.Results: In this study, there is a significant difference of leukocyte count, relative and absolute lymphocytes count, relative and absolute neutrophils count, and relative and absolute monocytes count from day 2 to day 6 of dengue infection (p value less than 0.05).Conclusion: Dengue patient have leucopenia on day 2 until day 6 of dengue fever. Lymphocytosis occurs on day 6 of dengue fever. Neutrophils decrease in early infection. Monocytes count is normal in dengue fever, but decrease in DHFKeywords: dengue in fection, leukocyte, lymphocytes, neutrophils, monocytes